The Hierarchy of Wāḍiḥ al-Dalālah in Uṣūl al-Fiqh: An Analysis of Ẓāhir, Naṣṣ, Mufassar, and Muḥkam in Legal Verses - Ahmad Solikin; Abad Badruzaman; Ishthifaul Ashfia (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2026)
The study of wāḍiḥ al-dalālah constitutes an important aspect of qawāʿid lughawiyyah in uṣūl al-fiqh, as it concerns the determination of the degree of semantic clarity in textual expressions (alfāẓ) in the process of understanding scriptural texts and deriving legal rulings. This study aims to analyze the hierarchy of ẓāhir, naṣṣ, mufassar, and muḥkam and examine its application to legal verses by taking into account the differences in the methodological frameworks of uṣūl al-fiqh scholars. This research employs a qualitative approach using library research. The data were obtained from classical and contemporary works on uṣūl al-fiqh, particularly the works of al-Sarakhsī, al-Āmidī, Qāḍī Abī Yaʿlā, al-Zarkashī, and ’Abd al-Wahhāb Khallāf. The data were analyzed through content analysis by identifying, categorizing, and comparing the characteristics of each category and applying them to Q.S. al-Baqarah [2]:228, Q.S. al-Nisā‘ [4]:3, and Q.S. al-Nūr [24]:4. The findings indicate that the hierarchy of wāḍiḥ al-dalālah cannot be applied mechanically solely on the basis of the degree of textual clarity. The analysis of the term qurū‘ in Q.S. al-Baqarah [2]:228 demonstrates that the existence of two possible meanings requires an examination of the strength of linguistic and juridical evidence before the expression can be categorized as ẓāhir. Q.S. al-Nisā‘ [4]:3 demonstrates that the determination of naṣṣ must take into account siyāq al-kalām and the relationship among textual expressions, rather than relying solely on the literal meaning of a particular phrase. Q.S. al-Nūr [24]:4 demonstrates that semantic clarity may apply to a particular expression or textual structure, such as the specification of thamānīna jaldah (eighty lashes), without automatically assigning the entire verse to a single category. Meanwhile, the expression abadan indicates that a linguistic meaning denoting continuity must be distinguished from the uṣūlī determination of muḥkam, which still requires examination of other evidences and the possibility of naskh. Thus, the study finds that wāḍiḥ al-dalālah functions as a framework for controlling interpretation, particularly in determining the strength of dalālah, limiting the scope of ta‘wīl, and supporting the process of tarjīḥ. However, the hierarchy does not automatically resolve legal issues; the determination of each category remains dependent on linguistic structure, siyāq, qarīnah, the relationship among evidences, and the methodological framework of uṣūl being employed.